Comparison of surgical site infection and wound dehiscence rates between primary and delayed primary closure of incision in ileal perforation patients - Qurashi, Sabrina Akhter; Aman, Asif; Mondal, Satya Ranjan; Ahmed, Jalal; Ullah, M. Meher; Rahman, A. Z. M. Mahfuzur (International Surgery Journal, 2025)
Background: Ileal perforation is a common surgical emergency associated with significant postoperative complications, particularly surgical site infection (SSI) and wound dehiscence. The method of wound closure, primary closure (PC) versus delayed primary closure (DPC), may influence these outcomes. This study aimed to compare the rates and timing of SSI and wound dehiscence between primary and delayed primary wound closure in patients undergoing surgery for ileal perforation. Methods: This quasi-experimental study was conducted at the Department of Surgery, Dhaka Medical College Hospital, Dhaka, Bangladesh, from September 2022 to August 2023. The study included 34 patients diagnosed with ileal perforation who underwent laparotomy at the Department of Surgery of Dhaka Medical College Hospital. All patients were equally allocated into two groups: Group A- Patients who underwent primary wound closure (PC), and Group B - Patients who underwent delayed primary wound closure (DPC). Result: The baseline characteristics (age, gender, and BMI) were similar between the groups (p>0.05). SSI occurred in all patients in Group A (100%) compared to only 8 patients (47.1%) in Group B, showing a significant reduction in SSI with DPC (p<0.001). Most SSIs in Group A occurred on the 5th POD, while in Group B, the peak was on the 10th POD. Partial wound dehiscence was significantly more common in Group A (64.7%) compared to Group B (23.5%) (p=0.038). Although complete dehiscence was higher in Group A (35.3%) than Group B (11.8%), the difference was not statistically significant (p=0.225). Notably, 64.7% of patients in the DPC group had no wound dehiscence, while none in the PC group avoided this complication (p<0.001). Conclusions: This study showed that delayed primary closure significantly reduces the incidence of surgical site infection and wound dehiscence in ileal perforation, making it a preferable option in ileal perforation case.